Perception of Words and Pitch Patterns in Song and Speech - Merrill, Julia; Sammler, Daniela; Bangert, Marc; Goldhahn, Dirk; Lohmann, Gabriele; Turner, Robert; Friederici, Angela D. (Frontiers in Psychology, 2012)
This fMRI study examines shared and distinct cortical areas involved in the auditory perception of song and speech at the level of their underlying constituents: words, pitch and rhythm. Univariate and multivariate analyses were performed on the brain activity patterns of six conditions, arranged in a subtractive hierarchy: sung sentences including words, pitch and rhythm; hummed speech prosody and song melody containing only pitch patterns and rhythm; as well as the pure musical or speech rhythm. Systematic contrasts between these balanced conditions following their hierarchical organization showed a great overlap between song and speech at all levels in the bilateral temporal lobe, but suggested a differential role of the inferior frontal gyrus (IFG) and intraparietal sulcus (IPS) in processing song and speech. The left IFG was involved in word- and pitch-related processing in speech, the right IFG in processing pitch in song. Furthermore, the IPS showed sensitivity to discrete pitch relations in song as opposed to the gliding pitch in speech. Finally, the superior temporal gyrus and premotor cortex coded for general differences between words and pitch patterns, irrespective of whether they were sung or spoken. Thus, song and speech share many features which are reflected in a fundamental similarity of brain areas involved in their perception. However, fine-grained acoustic differences on word and pitch level are reflected in the activity of IFG and IPS.